Synergistic effect of outer helical fins and hybrid nanofluid on hydrothermal performance of shell and two-coil heat exchanger - Wajdi Rajhi; Aymen h. Salih; As'ad Alizadeh; Kuwar Mausam; Aashim Dhawan; Rifaqat Ali; Sachin Mittal; Kaouther Ghachem; Walid Aich (Case Studies in Thermal Engineering)
Heat exchangers are frequently utilized in industrial applications such as power plants, refrigeration, chemical processing, and alternative energy systems. Improving thermal efficiency is critical for reducing energy consumption and ensuring operational sustainability. Conical coil heat exchangers have gained popularity due to their ability to generate secondary flow effects, which enhance convective heat transfer. However, despite their potential, the optimal coil configuration and nanofluid selection for maximum performance remain unknown. Previous research has primarily focused on traditional straight and helical coil designs, with limited attention paid to the effects of twisted tape inserts and helical fins in conical coil geometries. Furthermore, hybrid nanofluids have emerged as a potential alternative for enhancing heat exchanger efficiency, although their relative effectiveness in various conical coil topologies remains unknown. The thermal performance of a shell-and-conical-coil heat exchanger is investigated numerically in this work using a finite volume model. Three conical coil designs were studied: Case A, which included a twisted tape inside the coil; Case B, which used a twisted tape on the coil body as a helical fin; and Case C, which was a simple cone-shaped coil. The working fluids included hybrid nanofluids composed of (i) single-wall carbon nanotube (SWCNT)-multi-wall carbon nanotube (MWCNT), (ii) aluminium oxide (Al2O3)-titanium dioxide (TiO2), and (iii) molybdenum disulfide (MoS2)-iron oxide (II, III) oxide (Fe3O4), with water as the base fluid. At both low (De = 2550) and high (De = 4200) Dean numbers, Case A outperformed Case B by 14.3 % and 10.5 %, and Case C by 33.3 % and 52.7 %, respectively. The SWCNT-MWCNT/Water nanofluid outperformed Al2O3-TiO2/Water, MoS2-Fe3O4/Water, and pure water by up to 21.9 % and 9.4 %, respectively. It achieved the maximum thermal performance factor for both low and high Dean numbers. These findings demonstrate the efficacy of Case A (coil tube with a twisted tape) and hybrid nanofluids in enhancing heat exchanger performance under various flow conditions, providing valuable insights for future thermal system designs.